2012
DOI: 10.1017/s0021859612000573
|View full text |Cite
|
Sign up to set email alerts
|

Development of new quantitative physiological and molecular breeding parameters based on the sugar-beet vernalization intensity model

Abstract: SUMMARYSugar-beet crops, Beta vulgaris spp. vulgaris (L), suffer from premature bolting and flowering as a consequence of prolonged exposure to cold conditions (vernalization). This reduces crop yield and quality and could be avoided if bolting-resistant varieties were available. Traditionally, development of bolting-resistant varieties has relied on selection against the annual growth habit associated with the bolting gene B. However, this has failed to deliver crops that can be reliably sown in early spring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Such modified plants would possibly exhibit a diminished taproot sucrose release and therefore a reduced building block supply for inflorescence formation. This potential impact on bolting makes BvSUT4 a highly relevant target for breeding approaches (Pfeiffer et al, 2014;Chiurugwi et al, 2013) aiming at bolting resistance and at withholding cold-induced sucrose loss from taproots.…”
Section: Discussionmentioning
confidence: 99%
“…Such modified plants would possibly exhibit a diminished taproot sucrose release and therefore a reduced building block supply for inflorescence formation. This potential impact on bolting makes BvSUT4 a highly relevant target for breeding approaches (Pfeiffer et al, 2014;Chiurugwi et al, 2013) aiming at bolting resistance and at withholding cold-induced sucrose loss from taproots.…”
Section: Discussionmentioning
confidence: 99%
“…Although sugar beet cultivars carry the b allele , cold temperatures after sowing could vernalize the plants and lead to bolting before winter (Chiurugwi et al 2013;Milford et al 2010), often referred to as early bolting. As early bolting is undesired during crop production, this has always been addressed in breeding and resulted in improved early bolting resistance of modern cultivars (Milford et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are focusing on identifying sugar beet genes that are associated with hormonal status in Arabidopsis (gibberellin pathway (v)), as flowering in plants is influenced by their hormonal status. Chiurugwi et al (2012) discovered that during vernalization, the expression of the gibberellin oxidase gene BvGA20ox2 increases and the expression of BvGA20ox1 decreases in the leaves and apical meristem [97]. Mutasa-Göttgens et al (2009,2012) also observed an increase in the expression of BvGA20ox1 during the postvernalization period [45,98].…”
Section: Hormonal Control Of the Transition To Flowering In Sugar Beetmentioning
confidence: 99%